Microbial community and flavor analyses of fermented grains of Furou-type Baijiu - Tang, Yanyan; Liu, Yanbo; Zhang, Pengpeng; Liu, Hongliang; Wang, Yonghua; Li, Huawei; Zhu, Jinxiao; Pan, Chunmei (Frontiers in Microbiology, 2025)
IntroductionIn this study, we used single-molecule real-time sequencing to investigate the microbial community structure of jiuqu, pit mud, and fermented grains, before and after cellaring, in the brewing environment.MethodsWe detected the volatile flavor substances in the fermented grains using gas chromatography–mass spectrometry (GC–MS), and examined the changes in microbial community structure, before and after cellaring, as well as the correlation between flavor and microorganisms in Furou-type Baijiu. At the same time, the microbial traceability technique was used to investigate the contribution of fermented grains to the brewing microbiota, before and after cellaring.Results and discussionThe results showed that the microbial diversity and richness of the fermented grains were higher than those at the time of cellaring. The dominant bacterial species changed from Bacillus subtilis to Acetilactobacillus jinshanensis, and the dominant fungal genus, Saccharomyces sp., gradually increased. The relative abundance of Wickerhamomyces anomalus gradually decreased. The contents of acids, alcohols, and esters, before and after cellaring, were primarily influenced by the microbial community structure, while the relative amounts of flavor substances in fermented grains were significantly higher than those in stacked samples. The traceability analysis revealed that the microbial bacterial community in the fermented grains, both before and after entering the cellar, mainly originated from Fuqu and pit mud, while the fungal community primarily originated from Fuqu. This study offers insights into regulating of microbial community diversity to produce high-quality Furou-type Baijiu.